Effects of a Tart Cherry Supplement on Recovery from Exhaustive Exercise - Dolores G. Ortega; Jared W. Coburn; Andrew J. Galpin; Pablo B. Costa (Journal of Functional Morphology and Kinesiology, 2023)
The aim of this study was to investigate the effects of a tart cherry supplement on recovery from exercise-induced muscle damage. Seventeen recreationally active women (mean age ± SD = 22.2 ± 3.3 years, height = 162.0 ± 6.0 cm, body mass = 65.1 ± 11.1 kg, BMI = 24.7 ± 3.5 kg·m2) supplemented with 1000 mg of concentrated tart cherry or a placebo for eight consecutive days. An overload protocol of 8 sets of 10 repetitions of maximal effort concentric and eccentric muscle actions of the leg extensors at a velocity of 60<semantics>°·s−1</semantics> was performed on the fourth day of supplementation. Testing sessions consisted of a muscle function test (MFT) to examine pre- and post-testing peak torque, peak power, total work, time-to-peak torque, mean power, muscle activation of the quadriceps, and muscle soreness at baseline and post-testing at 0 h, 24 h, 48 h, and 72 h. A second trial of testing was repeated two weeks later using the opposite supplement to the one assigned for the first trial. No significant interaction for time × condition × velocity (p = 0.916) and no significant main effect for condition (p = 0.557) were demonstrated for peak torque. However, there were main effects for time and velocity for concentric quadriceps peak torque (p < 0.001). For muscle soreness, there was no two-way interaction for time x condition (p > 0.05) and no main effect for condition (p > 0.05), but there was a main effect for time (p < 0.001). In conclusion, a tart cherry supplement did not attenuate losses in isokinetic muscle peak torque, peak power, total work, time-to-peak torque, muscle soreness, or quadriceps muscle activation.